Kajian longitudinal terhadap prestasi guru baharu: pengaruh kesediaan guru praperkhidmatan, program latihan guru dan sosialisasi organisasi - Mohammad Yulan, A'ini Fariza (2019)
The learning process at a teaching institution is said to be an important element in determining the achievement of a future teacher. Past studies indicated that teachers' training programmes are closely linked to pre-service teachers' readiness to become teachers but the impact of learning experience on the institution is not studied longitudinally after the individual is in a real job situation. This study examined a hypothesized structural model that postulated socialization of the organization factors comprising context, content and social dimensions as mediators between the pre-service teachers' readiness and teacher training programme with novice teachers' performance. Based on Bandura's Social Cognitive Learning theory, Job Performance theory and the 3P Teaching and Learning model (Presage-Process-Product), a model of the relationship between the variables was built and tested using the Structural Equation Modeling. The sample consisted of 206 pre-service teachers who later became novice teachers. The longitudinal-panel study or long-term survey involved the collection of first phase data through pre-service teachers' readiness and teacher training programme questionnaires, while the second phase through organizational socialization and job performance questionnaires of the same individu after being placed in school as a novice teacher. The findings showed that preservice teachers' readiness, teacher training programme, content socialization, social socialization and novice teachers' performance are at a satisfactory level. All of these variables have significant positive relationships with each other. However, only the content and social socialization affected the performance of novice teachers while the pre-service teachers' readiness and teacher training programme are on the contrary. Practically, this study suggested that the teacher education institute context factors should be enhanced as well as the school context factors towards strengthening the performance of novice teachers. This study provided empirical evidence on the application of the 3P model in the context of institutional and longitudinal study.